Teacher Questioning as A Formative Assessment Strategy In EFL Context - Milawati, Milawati (Journal of English Language Teaching and Linguistics, 2017)
Existing studies on classroom questioning tend to focus on exploring effective teacher’s questioning in classroom learning and finding the relationship between questioning behavior and students outcomes, however, there has been scarce research on teacher questioning as a formative assessment strategy. It investigated how teachers deployed questions to stimulate student thinking, uncover students’ current level of learning, and allow responses to inform pedagogic decisions. The research method was classroom observations. This article highlights the practice of one experienced teacher who conducted quality questioning to gauge and facilitate learning. It also provides practical insights into how questioning can be developed as a formative assessment method and recommends equipping teachers with further knowledge and skills to carry out effective questioning.